Fast electrochromic switching of electrospun Cu-doped NiO nanofibers. (15th March 2020) - Li, Yuanyue; Cui, Youchao; Yao, Zhao; Liu, Guoxia; Shan, Fukai
Abstract: In this report, one-dimensional Cu-doped NiO nanofibers were synthesized by electrospinning and their electrochromic (EC) performance was investigated. It is demonstrated that the Ni0.97 Cu0.03 O nanofibers exhibit particularly fast switching speed (1.6 s for coloring and 0.9 s for bleaching) among NiO-based EC devices reported so far. Furthermore, other outstanding EC properties, including large transmittance modulation (73% at 550 nm), high coloration efficiency (77.9 cm 2 C −1 ) and good cycling durability (80% after 2000 cycles), were also achieved for Ni0.97 Cu0.03 O nanofibers. These attractive EC properties are attributed to their one-dimensional nanostructures with small size grains and superior electrical conductivity. Graphical abstract: Image, graphical abstract